2018
DOI: 10.1038/s41467-018-04559-0
|View full text |Cite
|
Sign up to set email alerts
|

Precise temporal regulation of alternative splicing during neural development

Abstract: Alternative splicing (AS) is one crucial step of gene expression that must be tightly regulated during neurodevelopment. However, the precise timing of developmental splicing switches and the underlying regulatory mechanisms are poorly understood. Here we systematically analyze the temporal regulation of AS in a large number of transcriptome profiles of developing mouse cortices, in vivo purified neuronal subtypes, and neurons differentiated in vitro. Our analysis reveals early-switch and late-switch exons in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
210
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(223 citation statements)
references
References 76 publications
13
210
0
Order By: Relevance
“…Transcriptional and post-transcriptional control of individual isoforms of genes is crucial for neuronal differentiation [1][2][3][4][5] , and isoforms of genes have been shown to be specific to cell-types in mouse and human brains [6][7][8][9][10][11] . It is therefore not surprising that dysregulation of splicing has been shown to be associated with several neurodevelopmental and neuropsychiatric diseases 3,12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional and post-transcriptional control of individual isoforms of genes is crucial for neuronal differentiation [1][2][3][4][5] , and isoforms of genes have been shown to be specific to cell-types in mouse and human brains [6][7][8][9][10][11] . It is therefore not surprising that dysregulation of splicing has been shown to be associated with several neurodevelopmental and neuropsychiatric diseases 3,12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Rbfox1 was identified in 1994 as the genomic locus feminizing on X (fox-1) in C. elegans; it was subsequently shown that the encoded protein peaks in expression in larval developmental stages and controls sex determination by repressing the dosage compensation factor xol-1 post-transcriptionally 1,2 . Mammalian Rbfox1 (A2BP1) and its paralogs Rbfox2 (RBM9) and Rbfox3 (NeuN) are highly expressed in heart, skeletal muscle, and in the adult brain, with a characteristic spike in expression in late neuronal development [3][4][5][6] . While Rbfox proteins are predominantly nuclear, where they regulate pre-mRNA splicing, some isoforms are also expressed in the cytoplasm, where they regulate RNA stability 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternative mRNAs may be generated from the same gene by inclusion or skipping of a particular exon in the mature transcript, in a process known as alternative splicing (AS) (19,36). There is evidence of AS for most mammalian genes (35,38) and of widespread changes of AS patterns throughout brain and heart development (4,5,15,18,23,42,43,56). Defects in mRNA processing of some specific genes often lead to disease (5,26,27) and have been associated with complex neurological disorders, such as autistic syndrome (23,28,42,55), and cancer (12,49).…”
Section: Introductionmentioning
confidence: 99%